The Role of Allium subhirsutum L. in the Attenuation of Dermal Wounds by Modulating Oxidative Stress and Inflammation in Wistar Albino Rats - Mongi Saoudi; Riadh Badraoui; Ahlem Chira; Mohd Saeed; Nouha Bouali; Salem Elkahoui; Jahoor M. Alam; Choumous Kallel; Abdelfattah El Feki (Molecules, 2021)
In our study, Allium subhirsutum L. (AS) was investigated to assess its phenolic profile and bioactive molecules including flavonoids and organosulfur compounds. The antioxidant potential of AS and wound healing activity were addressed using skin wound healing and oxidative stress and inflammation marker estimation in rat models. Phytochemical and antiradical activities of AS extract (ASE) and oil (ASO) were studied. The rats were randomly assigned to four groups: group I served as a control and was treated with simple ointment base, group II was treated with ASE ointment, group III was treated with ASO ointment and group IV (reference group; Ref) was treated with a reference drug “Cytolcentella® cream”. Phytochemical screening showed that total phenols (215 ± 3.5 mg GAE/g) and flavonoids (172.4 ± 3.1 mg QE/g) were higher in the ASO than the ASE group. The results of the antioxidant properties showed that ASO exhibited the highest DPPH free radical scavenging potential (IC50 = 0.136 ± 0.07 mg/mL), FRAP test (IC50 = 0.013 ± 0.006 mg/mL), ABTS test (IC50 = 0.52 ± 0.03 mg/mL) and total antioxidant capacity (IC50 = 0.34 ± 0.06 mg/mL). In the wound healing study, topical application of ASO performed the fastest wound-repairing process estimated by a chromatic study, percentage wound closure, fibrinogen level and oxidative damage status, as compared to ASE, the Cytolcentella reference drug and the untreated rats. The use of AS extract and oil were also associated with the attenuation of oxidative stress damage in the wound-healing treated rats. Overall, the results provided that AS, particularly ASO, has a potential medicinal value to act as effective skin wound healing agent.